OP0277 AURORA PHASE 3 STUDY DEMONSTRATES VOCLOSPORIN STATISTICAL SUPERIORITY OVER STANDARD OF CARE IN LUPUS NEPHRITIS (LN). (2nd June 2020) - Arriens, C.; Polyakova, S.; Adzerikho, I.; Randhawa, S.; Solomons, N.
Abstract : Background: Voclosporin (VCS) is a novel high potency calcineurin inhibitor (CNI) with a favorable metabolic profile and a consistent predictable dose response potentially eliminating the need for therapeutic drug monitoring. LN occurs more frequently and is more severe in Hispanic/Latino ethnicity SLE patients. The recently completed phase 3 AURORA study builds on the favorable efficacy seen in the Phase IIb AURA-LV study in patients with active LN. Objectives: Document efficacy and safety of VCS vs placebo over one year when used with 2 grams of MMF daily and a rapid steroid taper in patients with active LN. Methods: AURORA is a Phase III multicenter, randomized, double-blind, placebo-controlled 52-week study of active LN patients. Patients were randomized 1:1 to VCS (23.7 mg BID) or placebo in combination with mycophenolate (MMF, 1 g BID) and rapidly tapered oral steroids. The primary endpoint was renal response (RR) at 52 weeks, defined as UPCR of ≤ 0.5 mg/mg, eGFR ≥ 60 mL/min, or no confirmed decrease from baseline in eGFR of > 20%, presence of sustained, low dose steroids and no administration of rescue medication. Ethnicity subgroup analyses of RR was also undertaken given the higher severity of disease in the Hispanic/Latino LN patients. Results: There were 357 patients enrolled, 88% female, median age of 31 and 33% of Hispanic/Latino ethnicity. Renal response by intention to treat analysis at 52 weeks was 40.8% for the voclosporin arm and 22.5% for the control arm (OR: 2.65; 95% CI: 1.64, 4.27; p< 0.001); therefore, AURORA met its primary endpoint. These findings were consistent with those observed in the previously completed pivotal AURA-LV study. Ethnicity subgroup analysis of RR at 52 weeks noted benefit of VCS in both Hispanic/Latino (VCS 38.6% and control 18.6%, p=0.0062, OR 3.45) and non-Hispanic/Latino patients (VCS 41.8% and control 24.6%, p=0.0045, OR 2.29). The benefits of VCS were also seen for all pre-specified hierarchical secondary endpoints: RR at 24 weeks, partial renal response (PRR) at 24 and 52 weeks, time to achieve UPCR ≤ 0.5, and time to 50% reduction in UPCR. Furthermore, all pre-specified subgroup analyses (age, sex, race, biopsy class, region, and prior MMF use) favored VCS. VCS was well tolerated with no unexpected safety signals. The overall incidence of SAEs were similar in both groups (VCS 20.8% and control 21.3%); with infection most commonly reported (VCS 10.1% and control 11.2%). Overall mortality in the trial was low, with one death in the voclosporin arm and five in the control arm. Additionally, the VCS arm showed no significant decrease at week 52 in eGFR or increase in BP, lipids, or glucose. Conclusion: The AURORA study met its primary endpoint and VCS was efficacious in Hispanic/Latino ethnicity patients, a difficult to treat group. Disclosure of Interests: Cristina Arriens Grant/research support from: - BMS: Investigator Initiated Trial Research Funding, GSK: Investigator Initiated Trial Research Funding, Exagen: Research Grant, Consultant of: AstraZeneca (Sci Ad Board Dec 2017), GSK (Sci Ad Board Oct 2018), BMS (Sci Ad Board April 2019), Svetlana Polyakova: None declared, Igor Adzerikho: None declared, Simrat Randhawa Shareholder of: Aurinia Pharmaceuticals, Inc. stock, Employee of: Aurinia Pharmaceuticals, Inc., Neil Solomons Shareholder of: Aurinia Pharmaceuticals, Inc. stock, Employee of: Aurinia Pharmaceuticals.